ChemInform Abstract: Recent Advances on the Lewis Acid‐Catalyzed Cascade Rearrangements of Propargylic Alcohols and Their Derivatives. Issue 33 (19th August 2014) - Zhu, Yuanxun; Sun, Lang; Lu, Ping; Wang, Yanguang
Abstract Review: 71 refs.